Analisis Pengaruh Transaksi Non Tunai Terhadap Pertumbuhan Ekonomi Indonesia - Horinda Pertiwi; Jean Elikal Marna (Jurnal Salingka Nagari, 2023)
This study aims to determine the effect of non-cash transactions on Indonesia's economic growth in 2010-2020, with research variables including debit card transactions, credit card transactions, e-money, and Indonesia's economic growth rate in the last eleven years. This type of research is descriptive and associative research. This research uses Multiple Linear Regression analysis model with Ordinary Least Square (OLS) method. The data used in this study are secondary data with the nature of time series data from 2010-2020 obtained from the Central Statistics Agency and Bank Indonesia.The results of this study indicate that: debit card transactions have a significant effect on Indonesia's economic growth, credit card transactions have no significant effect on Indonesia's economic growth, e-money transactions have no significant effect on Indonesia's economic growth, and credit card, debit card, and e-money transactions simultaneously have a significant effect on Indonesia's economic growth.